Toward a bifurcated theory of emotional deterrence - Pickett, Justin T. (Criminology, 2018)
Since Hobbes (1957 [1651] and Beccaria (1963 [1764]), scholars have theorized that the emotion of fear is critical for deterrence. Nevertheless, contemporary deterrence researchers have mostly overlooked the distinction between perceived sanction risk and fear of apprehension. Whereas perceived risk is a cognitive judgment, fear involves visceral feelings of anxiety or dread. Equally important, a theory explicating the influence of deterrence on both criminal propensity and situational offending has remained elusive. We develop a theoretical model in which perceived risk and fear are distinguished at both the general and situational levels. We test this theoretical model with data from a set of survey‐based experiments conducted in 2016 with a nationwide sample of adults (N = 965). We find that perceived risk and fear are empirically distinct and that perceived risk is positively related to fear at both the general and situational levels. Certain background and situational factors have indirect effects through perceived risk on fear. In turn, perceived risk has indirect effects through fear on both criminal propensity and situational intentions to offend. Fear's inclusion increases explanatory power for both criminal propensity and situational offending intentions. Fear is a stronger predictor than either self‐control or prior offending of situational intentions to offend.